Pemanfaatan Teknologi Tepat Guna Sistem Sprinkle untuk Mendukung Produktivitas Pertanian di Desa Bendung Semin Gunungkidul - Waluyo, Joko; Sholeh, Muhammad; Syafriyudin, Syafriyudin; Rahayu, Suparni Setyowati; Purwanti, Noordiana Herry; Bikorin, Bikorin (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2025)
Increasing agricultural productivity is a key focus in supporting food security and the welfare of farmers.  One of the challenges in managing agricultural land in Bendung Village is the unpredictable availability of water and the reliance on traditional irrigation methods.  This often hampers the optimization of agricultural yields. This community service aims to apply an appropriate technology in the form of a sprinkler irrigation system as an innovative solution to improve the efficiency of irrigating agricultural land in Bendung Village. The sprinkler system used is supported by a renewable energy source in the form of a Solar Power Plant (PLTS), so that it is more environmentally friendly and sustainable. The methods used included socialization and training of farmers regarding the use and maintenance of sprinkler systems, as well as monitoring the impact of the application of this technology on crop productivity. The evaluation results showed a significant improvement in water usage and time efficiency. The irrigation process using the old system took about 2-3 hours of watering labor on a 600 m2 field, while using sprinklers, farmers only need about 30 minutes. The implementation of the sprinkler system not only reduces operational costs but also makes water use more efficient and lowers total costs significantly. With a total water saving of about 41.6%, this technology provides long-term financial benefits to farmers in Bendung Village. Additionally, the system's relatively easy maintenance also adds value to the farm's sustainability and efficiency. This renewable energy-based sprinkler system can be a model for effective and sustainable irrigation solutions for other agricultural areas